La construcció literària de la irrealitat: ucronies i metàfores de decepció - Martínez-Gil, Víctor (Studia Romanica Posnaniensia, 2025)
As there are differences between possible worlds and fictional ones, there are also many types of literary unrealities, which this paper aims to classify. Works and genres will be analyzed from the perspective of counterfactuals and their relationships with the fictional pact and the willing suspension of disbelief. From here, the paper will focus on the description of those works that build an absolute, conceptual unreality. This unreality will be analyzed in two distinct ways: alternate histories and metaphors of disappointment as cataphoric forms. The paper will describe Catalan literature under these two perspectives.